Sharia Economy Provides Welfare for the Community - Syifa Destya Salsabila; Fifi Aprilia Yulianti; Zidna Rizka Maulida Sandy; Ade Gunawan; Ria Anisatus Sholihah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The meaning of welfare in sharia economics aims to achieve a person's general welfare, namely material, spiritual and moral welfare. The concept of Islamic economic benefits is based not only on the manifestation of economic values, but also on spiritual and moral values. This research was conducted based on a literature study with various references to journals and books as well as several articles. After all the data has been collected successfully collected during the research process both primary data and secondary data were analyzed qualitatively and then presented descriptively. Sharia economics with principles based on the Qur'an and As-Sunnah can be a solution for the benefit of society. And the government has made various efforts to stabilize inflation in the Islamic economy such as increasing the level of costs on individual income, also using reserves stored in the Baitul Mal, by using zakat or tax proceeds that are not spent in a certain period. Seeing the current conditions, the choice to develop Micro, Small and Medium Enterprises (MSMEs) is the right choice in order to reduce unemployment and absorb the existing workforce by opening new jobs. Suggestions for this research are so that the Indonesian economy can be better and continue to advance as a result of the slump of covid 19 with sharia economics and still hold on to the principles based on the Qur'an and As-Sunnah.